Motives of Honor, Pleasure, and Profit : Plantation Management in the Colonial Chesapeake, 1607-1763 - Walsh, Lorena Seebach, 1944- (Book collections on Project MUSE., 2010)
Lorena Walsh offers an enlightening history of plantation management in the Chesapeake colonies of Virginia and Maryland, ranging from the founding of Jamestown to the close of the Seven Years' War and the end of the "Golden Age" of colonial Chesapeake agriculture. She argues that, in the mid-17th century, planter elites deliberately chose to embrace slavery. Accounts of personal and family fortunes among the privileged minority and the less well documented accounts of the lives of the enslaved workers add a personal dimension to more concrete measures of planter success or failure